Potassium titanate whisker filled POM / UHMWPE composite material and preparation method thereof

CN121517851BActive Publication Date: 2026-10-27POLYSTAR ENG PLASTICS (SHANGHAI) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202511884692.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-12-15
Publication Date
2026-10-27
Estimated Expiration
2045-12-15

AI Technical Summary

Technical Problem

然而,这些方法均存在一定局限:聚合物共混易引起相容性问题,导致力学性能下降;润滑油脂虽用量较少,但可能影响热稳定性;碳纤维增强效果显著但成本较高,且制品表面质量不佳

Benefits of technology

[0017]本发明通过采用特定的钛酸钾晶须、相容剂,合理调控各组分之间的添加量,在POM基料、UHMWPE基料中各组分间相互协同,获得了更低的摩擦系数,更高的表面硬度,更优耐磨性能的复合材料。同时,该材料还具有较好的力学性能,可用于汽车后视镜轴承保持架、齿轮等组件。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121517851B_ABST
    Figure CN121517851B_ABST
Patent Text Reader

Abstract

The application provides a kind of potassium titanate whisker filled POM / UHMWPE composite material and a preparation method thereof.The composite material comprises the following raw material components by weight parts: POM 60~80%, UHMWPE 5~10%, potassium titanate whisker 10%~30%, lubricant 0.2%~0.5%, compounded antioxidant 0.2%~0.5%, the diameter of the potassium titanate whisker is 0.2~0.6 μm, the length is 10~20 μm, a composite material with lower friction coefficient, higher surface hardness and more optimal wear resistance is obtained, and the material also has good mechanical properties, and can be used for automobile rearview mirror bearing retainer, gear and other components.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of materials preparation technology and relates to a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. Background Technology

[0002] Polyoxymethylene (POM) is a high-performance polymer material with mechanical properties close to those of metals. It has high specific strength and specific stiffness, as well as advantages such as self-lubrication, wear resistance, excellent electrical insulation, fatigue resistance and creep resistance. Therefore, it is gradually replacing metal parts in aerospace, automobile manufacturing, precision instruments and electronic appliances and is used to manufacture various transmission structures.

[0003] Although polyoxymethylene (POM) possesses certain wear-resistant properties, frictional heat under high-speed, high-load conditions can lead to localized softening and deformation of the material. As modern equipment evolves towards miniaturization, high speed, and high performance, transmission components often operate under high temperature, high pressure, and rapid sliding conditions, placing higher demands on their wear resistance. Common approaches to improving POM wear resistance include: blending with organic polymers such as polytetrafluoroethylene (PTFE) and ultra-high molecular weight polyethylene (UHMWPE) to prepare alloys; incorporating lubricating greases such as silicone oil; or introducing inorganic fillers such as graphite, carbon fiber, and potassium titanate whiskers. However, these methods all have limitations: polymer blending easily causes compatibility issues, leading to a decrease in mechanical properties; although lubricating greases are used in small quantities, they may affect thermal stability; carbon fiber reinforcement is effective but costly, and the surface quality of the finished product is poor. Therefore, developing a multi-component synergistic modification composite system has become an effective way to achieve a balance between high wear resistance and high rigidity in POM. Summary of the Invention

[0004] To address the problems existing in the prior art, the present invention adopts the following technical solution:

[0005] In a first aspect, a potassium titanate whisker-filled POM / UHMWPE composite material is provided, wherein the composite material comprises the following raw material components by weight: 60-80% POM, 5-10% UHMWPE, 10-30% potassium titanate whiskers, 0.2-0.5% lubricant, and 0.2-0.5% compounded antioxidant, wherein the potassium titanate whiskers are modified potassium titanate whiskers obtained by sequentially treating with a pretreatment agent and a coupling agent.

[0006] As a preferred embodiment of the present invention, the potassium titanate whiskers have a diameter of 0.2~0.6μm and a length of 10~20μm.

[0007] As a preferred embodiment of the present invention, the composite material further includes a compatibilizer, wherein the mass ratio of the compatibilizer to potassium titanate whiskers is 1:(8~10).

[0008] As a preferred embodiment of the present invention, the melt flow index of the POM at 190°C / 2.16 kg is 10-20 g / 10 min.

[0009] As a preferred embodiment of the present invention, the UHMWPE has a melt index of 3-7 g / 10 min at 190°C / 2.16 kg.

[0010] As a preferred embodiment of the present invention, the processing procedure for the modified potassium titanate whiskers is as follows: potassium titanate whiskers are reacted with a pretreatment agent to obtain intermediate potassium titanate whiskers, and the intermediate potassium titanate whiskers are reacted with a coupling agent to obtain modified potassium titanate whiskers; the amount of the pretreatment agent added is 1.2~2.4% of the mass of the potassium titanate whiskers; the amount of the coupling agent added is 2~4% of the mass of the intermediate potassium titanate whiskers.

[0011] As a preferred embodiment of the present invention, the lubricant is a mixture of copolymer and bead-like or flake-like wax.

[0012] As a preferred embodiment of the present invention, the antioxidant is selected from one or a combination of antioxidant 1076, antioxidant 1010, antioxidant CA, antioxidant 2246, antioxidant 168, antioxidant 1098, and antioxidant 626.

[0013] Secondly, the present invention provides a method for preparing the aforementioned potassium titanate whisker-filled POM / UHMWPE composite material, the method comprising the following steps:

[0014] Weigh out the prescribed amounts of POM, UHMWPE, lubricant, compound antioxidant and compatibilizer and mix them in a high-speed mixer to obtain a mixture. The mixture is fed from the main feed port of a twin-screw extruder, and potassium titanate whiskers are fed from the side feed port for extrusion granulation.

[0015] As a preferred embodiment of the present invention, the processing temperature of the twin-screw extruder is 180~200 ℃, the screw speed is 240~360 r / min, the length of the strip passing through water is 1~2m, and the water temperature is controlled at 20~40℃.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] This invention utilizes specific potassium titanate whiskers and compatibilizers, and rationally controls the addition amounts of each component to achieve synergistic effects between the components in POM and UHMWPE base materials, resulting in a composite material with a lower coefficient of friction, higher surface hardness, and superior wear resistance. Simultaneously, this material also possesses good mechanical properties and can be used in components such as automotive rearview mirror bearing cages and gears. Attached Figure Description

[0018] Figure 1This is a photograph of the composite material prepared according to the present invention before the wear index test.

[0019] Figure 2 This is a photograph of the actual object used in the composite material wear index test. Detailed Implementation

[0020] To better illustrate the present invention and facilitate understanding of its technical solutions, the present invention will be further described in detail below. However, the following embodiments are merely simplified examples of the present invention and do not represent or limit the scope of protection of the present invention. The scope of protection of the present invention is determined by the claims.

[0021] The present invention provides a potassium titanate whisker-filled POM / UHMWPE composite material, wherein the composite material comprises the following raw material components in weight percentage: POM 60~80%, UHMWPE 5~10%, potassium titanate whiskers 10%~30%, lubricant 0.2%~0.5%, and compounded antioxidant 0.2%~0.5%.

[0022] As a preferred embodiment of the present invention, the POM is polyoxymethylene, with a melt index of 10-20 g / 10 min at 190°C / 2.16 kg. As a more preferred embodiment of the present invention, the POM has a melt index of 15 g / 10 min at 190°C / 2.16 kg.

[0023] In a preferred embodiment of the present invention, the UHMWPE is ultra-high molecular weight polyethylene with a melt index of 3-7 g / 10 min at 190°C / 2.16 kg. In a more preferred embodiment, the UHMWPE has a melt index of 5 g / 10 min at 190°C / 2.16 kg. All melt indices in this invention are obtained by testing according to ISO 113 standard.

[0024] As a preferred embodiment of the present invention, the weight percentage content of POM may be 60%, 64%, 68%, 72%, 76% or 80%, etc., but is not limited to the listed values, and other unlisted values ​​within this range are also applicable; the weight percentage content of UHMWPE may be 5%, 6%, 7%, 8%, 9% or 10%, etc., but is not limited to the listed values, and other unlisted values ​​within this range are also applicable.

[0025] As a more preferred embodiment of the present invention, the potassium titanate whiskers are modified potassium titanate whiskers obtained by sequentially treating with a pretreatment agent and a coupling agent. The treatment process of the modified potassium titanate whiskers is as follows: the potassium titanate whiskers are reacted with the pretreatment agent to obtain intermediate potassium titanate whiskers, and the intermediate potassium titanate whiskers are reacted with the coupling agent to obtain modified potassium titanate whiskers.

[0026] As a more preferred embodiment of the present invention, the processing procedure for the modified potassium titanate whiskers is as follows: the potassium titanate whiskers are vacuum dried at 100~120°C for 10~12h, dispersed in dehydrated toluene, and a pretreatment agent is slowly added dropwise under nitrogen and reflux at 80°C. After reacting for 4~6h, the mixture is vacuum filtered and washed with anhydrous toluene, and then vacuum dried at 60°C for 1~2h to obtain intermediate potassium titanate whiskers; the intermediate potassium titanate whiskers are redispersed in dehydrated toluene, and a coupling agent is slowly added dropwise under nitrogen and reflux at 80°C. After reacting for 6~8h, the mixture is vacuum filtered and washed with anhydrous toluene, and then vacuum dried at 60°C for 6~12h to obtain modified potassium titanate whiskers.

[0027] As a more preferred embodiment of the present invention, the amount of the pretreatment agent added is 1.2 to 2.4% of the mass of potassium titanate whiskers; the amount of the coupling agent added is 2 to 4% of the mass of intermediate potassium titanate whiskers.

[0028] As a more preferred embodiment of the present invention, the pretreatment agent is (3-isocyanopropyl)triethoxysilane. As a more preferred embodiment of the present invention, the coupling agent is methyloctadecyl(3-phenylpropyl)chlorosilane.

[0029] As a more preferred embodiment of the present invention, the potassium titanate whiskers have a diameter of 0.2~0.6μm and a length of 10~20μm.

[0030] As a more preferred embodiment of the present invention, the weight percentage content of the potassium titanate whiskers may be 10%, 14%, 18%, 22%, 26% or 30%, etc., but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0031] In a more preferred embodiment of the present invention, the potassium titanate whiskers and intermediate potassium titanate whiskers are dispersed in dehydrated toluene, and the solid-liquid ratio (g / mL) is controlled at 1:(16~20); the pretreatment agent and coupling agent are diluted with anhydrous toluene to 2~4 times their own volume and slowly added dropwise for reaction. In a more preferred embodiment of the present invention, the solid-liquid ratio (g / mL) is 1:18; the pretreatment agent and coupling agent are diluted with anhydrous toluene to 3 times their own volume and slowly added dropwise for reaction.

[0032] As a preferred embodiment of the present invention, the lubricant is a mixture of copolymer and bead-like or flake-like wax.

[0033] As a more preferred embodiment of the present invention, the weight percentage content of the lubricant may be 0.2%, 0.3%, 0.4% or 0.5%, etc., but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0034] In a preferred embodiment of the present invention, the antioxidant is selected from one or more combinations of antioxidant 1076, antioxidant 1010, antioxidant CA, antioxidant 2246, antioxidant 168, antioxidant 1098, and antioxidant 626; in a preferred embodiment of the present invention, the antioxidant includes antioxidant 168 and antioxidant 1010; in a preferred embodiment of the present invention, the mass ratio of antioxidant 168 to antioxidant 1010 is 1:(0.9-1.1); in a preferred embodiment of the present invention, the mass ratio of antioxidant 168 to antioxidant 1010 is 1:1.

[0035] As a more preferred embodiment of the present invention, the antioxidant content by weight percentage may be 0.2%, 0.3%, 0.4% or 0.5%, etc., but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0036] As a preferred embodiment of the present invention, the composite material further includes a compatibilizer, wherein the mass ratio of the compatibilizer to potassium titanate whiskers is 1:(8~10).

[0037] As a preferred embodiment of the present invention, the compatibilizer is an ethylene terpolymer with a melt index of 20 g / 10 min at 190°C / 2.16 kg and a melting point of 80°C.

[0038] The specific embodiments section of this invention also provides a method for preparing the aforementioned potassium titanate whisker-filled POM / UHMWPE composite material, the method comprising the following steps:

[0039] Weigh out the prescribed amounts of POM, UHMWPE, lubricant, compound antioxidant and compatibilizer and mix them in a high-speed mixer to obtain a mixture. The mixture is fed from the main feed port of a twin-screw extruder, and potassium titanate whiskers are fed from the side feed port for extrusion granulation.

[0040] As a preferred embodiment of the present invention, the mixing and processing time is 4 min to 6 min, for example, 4 min, 5 min or 6 min, but is not limited to the listed values. Other unlisted values ​​within this range are also applicable.

[0041] As a preferred embodiment of the present invention, the processing temperature of the twin-screw extruder is 180℃-200℃, such as 180℃, 185℃, 190℃, 195℃, or 200℃, but is not limited to the listed values; other unlisted values ​​within this range are also applicable. The screw speed of the twin-screw extruder is 240rpm-360rpm, such as 240rpm, 260rpm, 280rpm, 300rpm, 320rpm, 340rpm, or 360rpm, but is not limited to the listed values; other unlisted values ​​within this range are also applicable. The strip water passage length is 1-2m, such as 1m, 1.2m, 1.4m, 1.6m, 1.8m. m or 2m, etc., but not limited to the listed values; other unlisted values ​​within this range also apply; water temperature is controlled between 20℃ and 40℃, such as 20℃, 25℃, 30℃, 35℃ or 40℃, etc., but not limited to the listed values; other unlisted values ​​within this range also apply.

[0042] The following are typical but non-limiting embodiments of the present invention:

[0043] The following examples use POM (grade H140-54C, Changchun Artificial Resin Factory); UHMWPE (grade LY1040, Mitsui Chemicals, Japan); potassium titanate whiskers (TISMO N, Otsuka Chemicals, Japan); lubricant (grade P130, Brügmann); antioxidants including antioxidant 168 and antioxidant 1010 (BASF, Germany), wherein the mass ratio of antioxidant 168 to antioxidant 1010 is 1:1; compatibilizer (LOTADER 5500, Arkema).

[0044] Example 1:

[0045] This embodiment provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material includes the following raw material components in weight percentage: POM: 70%, UHMWPE: 7%, potassium titanate whiskers: 20%, lubricant: 0.3%, compounded antioxidant: 0.4%, compatibilizer: 2.3%.

[0046] The potassium titanate whiskers are modified potassium titanate whiskers obtained by sequentially treating with a pretreatment agent and a coupling agent. The treatment process is as follows: the potassium titanate whiskers are vacuum dried at 110°C for 11 hours, dispersed in dehydrated toluene, and the pretreatment agent is slowly added dropwise under nitrogen and reflux at 80°C. After reacting for 5 hours, the mixture is vacuum filtered and washed with anhydrous toluene, and then vacuum dried at 60°C for 2 hours to obtain intermediate potassium titanate whiskers. The intermediate potassium titanate whiskers are redispersed in dehydrated toluene, and the coupling agent is slowly added dropwise under nitrogen and reflux at 80°C. After reacting for 7 hours, the mixture is vacuum filtered and washed with anhydrous toluene, and then vacuum dried at 60°C for 9 hours to obtain modified potassium titanate whiskers. The pretreatment agent is (3-isocyanopropyl)triethoxysilane, and the amount added is 1.8% of the mass of the potassium titanate whiskers. The coupling agent is methyloctadecyl(3-phenylpropyl)chlorosilane, and the amount added is 3% of the mass of the intermediate potassium titanate whiskers.

[0047] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is as follows:

[0048] The formulated amounts of POM, UHMWPE, lubricant, compound antioxidant, and compatibilizer are mixed in a high-speed mixer to obtain a mixture. The mixture is fed from the main feed port of a twin-screw extruder, while potassium titanate whiskers are fed from the side feed port for extrusion granulation. The mixing and processing time is 5 minutes, the processing temperature of the twin-screw extruder is 190℃, and the screw speed is 300 r / min. The length of the material passing through water is 1.5m, and the water temperature is controlled at 30℃.

[0049] Example 2:

[0050] This embodiment provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material includes the following components in weight percentage: POM: 80%, UHMWPE: 8%, potassium titanate whiskers: 10%, lubricant: 0.3%, compounded antioxidant: 0.5%, compatibilizer: 1.2%.

[0051] The processing procedure for the potassium titanate whiskers is the same as that in Example 1.

[0052] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0053] Example 3:

[0054] This embodiment provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material includes the following components in weight percentage: POM: 60%, UHMWPE: 5.5%, potassium titanate whiskers: 30%, lubricant: 0.4%, compounded antioxidant: 0.4%, and compatibilizer: 3.7%.

[0055] The processing procedure for the potassium titanate whiskers is the same as that in Example 1.

[0056] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0057] Comparative Example 1:

[0058] This comparative example provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material comprises the following raw material components in weight percentage: POM: 70%, UHMWPE: 7%, potassium titanate whiskers: 20%, lubricant: 0.3%, compounded antioxidant: 0.4%, and compatibilizer: 2.3%.

[0059] The potassium titanate whiskers are modified potassium titanate whiskers obtained by sequentially treating them with a pretreatment agent and a coupling agent. The treatment process is the same as in Example 1, except that the diameter of the potassium titanate whiskers is 0.1~0.3μm and the length is 5μm. They were purchased from Nantong Aoxin Electronics AX-316-2.

[0060] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0061] Comparative Example 2:

[0062] This comparative example provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material comprises the following raw material components in weight percentage: POM: 70%, UHMWPE: 7%, potassium titanate whiskers: 20%, lubricant: 0.3%, compounded antioxidant: 0.4%, and compatibilizer: 2.3%. The compatibilizer is an ethylene terpolymer with a melt index of 7 g / 10 min at 190°C / 2.16 kg and a melting point of 65°C, purchased from Arkema LOTADER 4700.

[0063] The processing procedure for the potassium titanate whiskers is the same as that in Example 1.

[0064] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0065] Comparative Example 3:

[0066] This comparative example provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material comprises the following raw material components in weight percentage: POM: 70%, UHMWPE: 7%, potassium titanate whiskers: 20%, lubricant: 0.3%, compounded antioxidant: 0.4%, and compatibilizer: 2.3%. The compatibilizer is an ethylene terpolymer with a melt index of 40 g / 10 min at 190°C / 2.16 kg and a melting point of 102°C, purchased from Arkema LOTADER 6200.

[0067] The processing procedure for the potassium titanate whiskers is the same as that in Example 1.

[0068] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0069] Comparative Example 4:

[0070] This comparative example provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material comprises the following raw material components in weight percentage: POM: 70%, UHMWPE: 7%, potassium titanate whiskers: 20%, lubricant: 0.3%, compounded antioxidant: 0.4%, and compatibilizer: 2.3%.

[0071] The potassium titanate whiskers are modified potassium titanate whiskers obtained by sequentially treating them with a pretreatment agent and a coupling agent. The treatment process is the same as in Example 1, except that the coupling agent is octadecyldimethylmethoxysilane.

[0072] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0073] Comparative Example 5:

[0074] This comparative example provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material comprises the following raw material components in weight percentage: POM: 70%, UHMWPE: 7%, potassium titanate whiskers: 20%, lubricant: 0.3%, compounded antioxidant: 0.4%, and compatibilizer: 2.3%.

[0075] The potassium titanate whiskers are modified potassium titanate whiskers obtained by sequentially treating them with a pretreatment agent and a coupling agent. The treatment process is the same as in Example 1, except that the pretreatment agent is KH560.

[0076] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0077] Comparative Example 6:

[0078] This comparative example provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material comprises the following raw material components in weight percentage: POM: 70%, UHMWPE: 7%, potassium titanate whiskers: 20%, lubricant: 0.3%, compounded antioxidant: 0.4%, and compatibilizer: 2.3%.

[0079] The potassium titanate whiskers are modified potassium titanate whiskers obtained by sequentially treating with a pretreatment agent and a coupling agent. The treatment process is as follows: the potassium titanate whiskers are vacuum dried at 110°C for 11 hours, dispersed in dehydrated toluene, and the pretreatment agent and coupling agent are slowly added dropwise under nitrogen and reflux at 80°C. After reacting for 5 hours, the mixture is vacuum filtered and washed with anhydrous toluene, and then vacuum dried at 60°C for 9 hours to obtain intermediate potassium titanate whiskers. The pretreatment agent is (3-isocyanopropyl)triethoxysilane, and the amount added is 1.8% of the mass of the potassium titanate whiskers. The coupling agent is methyloctadecyl(3-phenylpropyl)chlorosilane, and the amount added is 3% of the mass of the potassium titanate whiskers.

[0080] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0081] Comparative Example 7:

[0082] This comparative example provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material comprises the following raw material components in weight percentage: POM: 70%, UHMWPE: 7%, potassium titanate whiskers: 20%, lubricant: 0.3%, compounded antioxidant: 0.4%, and compatibilizer: 2.3%.

[0083] The potassium titanate whiskers are modified potassium titanate whiskers obtained by sequentially treating with a pretreatment agent and a coupling agent. The treatment process is as follows: potassium titanate whiskers are dispersed in dehydrated toluene, and a coupling agent is slowly added dropwise under nitrogen and reflux at 80°C. After reacting for 7 hours, the mixture is vacuum filtered and washed with anhydrous toluene, and then vacuum dried at 60°C for 9 hours to obtain modified potassium titanate whiskers. The coupling agent is methyloctadecyl(3-phenylpropyl)chlorosilane, and the amount added is 3% of the mass of the potassium titanate whiskers.

[0084] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0085] Comparative Example 8:

[0086] This embodiment provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material includes the following raw material components in weight percentage: POM: 70%, UHMWPE: 7%, potassium titanate whiskers: 20%, lubricant: 0.3%, compounded antioxidant: 0.4%, compatibilizer: 2.3%.

[0087] The potassium titanate whiskers are modified potassium titanate whiskers obtained by sequentially treating with a pretreatment agent and a coupling agent. The treatment process is as follows: the potassium titanate whiskers are vacuum dried at 110°C for 11 hours, dispersed in dehydrated toluene, and the pretreatment agent is slowly added dropwise under nitrogen and reflux at 80°C. After reacting for 5 hours, the mixture is vacuum filtered and washed with anhydrous toluene, and then vacuum dried at 60°C for 2 hours to obtain modified potassium titanate whiskers. The pretreatment agent is (3-isocyanopropyl)triethoxysilane, and the amount added is 1.8% of the mass of the potassium titanate whiskers.

[0088] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0089] Comparative Example 9:

[0090] This embodiment provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material includes the following raw material components in weight percentage: POM: 70%, UHMWPE: 7%, potassium titanate whiskers: 20%, lubricant: 0.3%, compounded antioxidant: 0.4%, compatibilizer: 2.3%.

[0091] The potassium titanate whiskers are modified potassium titanate whiskers obtained by pretreatment. The pretreatment process is as follows: the potassium titanate whiskers are vacuum dried at 110°C for 11 hours, dispersed in dehydrated toluene, and the pretreatment agent is slowly added dropwise under nitrogen and reflux at 80°C. After reacting for 5 hours, the mixture is vacuum filtered and washed with anhydrous toluene, and then vacuum dried at 60°C for 2 hours to obtain modified potassium titanate whiskers. The pretreatment agent is KH560, and the amount added is 1.8% of the mass of the potassium titanate whiskers.

[0092] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0093] Comparative Example 10:

[0094] This embodiment provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material includes the following raw material components in weight percentage: POM: 70%, UHMWPE: 7%, potassium titanate whiskers: 20%, lubricant: 0.3%, compounded antioxidant: 0.4%, compatibilizer: 2.3%.

[0095] The potassium titanate whiskers are not pretreated or modified.

[0096] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0097] Comparative Example 11:

[0098] This comparative example provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material comprises the following raw material components in weight percentage: POM: 70%, UHMWPE: 7%, potassium titanate whiskers: 35%, lubricant: 0.3%, compounded antioxidant: 0.4%, and compatibilizer: 2.3%.

[0099] The processing procedure for the potassium titanate whiskers is the same as that in Example 1.

[0100] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0101] Comparative Example 12:

[0102] This comparative example provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material comprises the following raw material components in weight percentage: POM: 70%, UHMWPE: 7%, potassium titanate whiskers: 20%, lubricant: 0.3%, compounded antioxidant: 0.4%, and compatibilizer: 0%.

[0103] The processing procedure for the potassium titanate whiskers is the same as that in Example 1.

[0104] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0105] Comparative Example 13:

[0106] This comparative example provides a potassium titanate whisker-filled POM / UHMWPE composite material and its preparation method. The composite material comprises the following raw material components in weight percentage: POM: 70%, UHMWPE: 7%, potassium titanate whiskers: 0%, lubricant: 0.3%, compounded antioxidant: 0.4%, and compatibilizer: 2.3%.

[0107] The preparation method of the potassium titanate whisker-filled POM / UHMWPE composite material is the same as that in Example 1.

[0108] Performance tests were conducted on the potassium titanate whisker-filled POM / UHMWPE composite materials in Examples 1-3 and Comparative Examples 1-13, using ISO standards. The abrasion index test method involved using a Taber dual-head abrasion tester with a CS-10 grinding wheel, applying a 1000GR load, and setting the rotation speed to 10000 rpm. After reaching the specified rotation speed, the specimen was removed, and the condition of the specimen after abrasion or the difference in weight between the specimen before and after the test was observed. The abrasion index was calculated as: weight loss due to abrasion / number of test rotations × 1000. Note: Considering the influence of moisture content in the composite material parts, the parts were dried before and after the test at 90℃ for 8 hours. The composite material was processed into a 120*80*3mm color plate with an 8mm diameter hole in the center. A photograph of the part before testing is attached. Figure 1 As shown in the attached photos, the test was conducted successfully. Figure 2 As shown.

[0109] Dynamic friction coefficient test method: A BRUKER UMT-2 friction and wear testing machine was used, employing a ball-disc test method. The ball was made of modified plastic, and the disc was made of GCR15 bearing steel. The applied force was 10 N, and the rotational speed was 100 mm / s. The test results are shown in Tables 1 and 2 below.

[0110] Table 1: Performance test results of composite materials in Examples 1-2 and Comparative Examples 1-4

[0111]

[0112] Table 2: Test results of composite material properties in Comparative Examples 5-13

[0113]

[0114] As can be seen from the comparison in Tables 1 and 2, in Example 1 and Comparative Example 1, when the length of the potassium titanate whiskers is short, the flexural modulus, hardness, and wear resistance of the composite material all decrease, while the impact toughness also decreases. In Comparative Examples 2 and 3, when ethylene terpolymers with different melt indices and melting points are used as compatibilizers, the mechanical and frictional properties of the materials are affected. In Comparative Example 12, without the addition of a compatibilizer, the impact strength and wear resistance of the material decrease, while the coefficient of friction increases. In Comparative Example 13, without the addition of potassium titanate whiskers, the rigidity, hardness, and wear resistance of the material are significantly affected. This further illustrates that selecting and adding specific potassium titanate whiskers and compatibilizers in the system of this invention is beneficial to achieving a better balance between overall mechanical properties and wear resistance.

[0115] In Comparative Examples 4 and 5, replacing the coupling agent with octadecyldimethylmethoxysilane and the pretreatment agent with KH560, respectively, resulted in an increase in both the friction coefficient and the wear index. This may be because the interfacial bonding force between the potassium titanate whiskers and the POM matrix weakened, and the interfacial stability decreased, making the interface more susceptible to damage during friction. Specifically, in Comparative Example 6, potassium titanate whiskers were modified using both the pretreatment agent and the coupling agent; in Comparative Example 7, potassium titanate whiskers were only coupled without pretreatment; in Comparative Example 8, potassium titanate whiskers were only pretreated; in Comparative Example 9, potassium titanate whiskers were modified with KH560; and in Comparative Example 10, potassium titanate whiskers were not modified. In these cases, the mechanical strength and wear resistance of the materials decreased significantly, and the impact toughness was also poor. In other words, the applicant unexpectedly discovered that in the system of the present invention, only by first pretreating with (3-isocyanopropyl)triethoxysilane and then modifying it with methyloctadecyl(3-phenylpropyl)chlorosilane can the modified potassium titanate whiskers interact better with other components in the matrix, resulting in a composite material with excellent comprehensive performance.

[0116] In Comparative Example 11, when the amount of potassium titanate whiskers added was 35% and the compatibilizer was 2.3%, although the rigidity of the material was further improved, the impact toughness was significantly deteriorated, and the coefficient of friction also increased significantly. This may be because the excessive rigid filler accumulates in the matrix, resulting in dense stress concentration points, which restricts the plastic deformation ability of the polymer phase, leading to the deterioration of impact toughness. At the same time, the excessive whiskers reduce the adhesion to the matrix, making the whiskers easy to fall off and increasing the coefficient of friction. Only when the mass ratio of compatibilizer to potassium titanate whiskers is limited to 1:(8~10), the two work together to ensure that the compatibilizer can fully coat and wet the surface of the potassium titanate whiskers, achieving a balance between toughness and wear resistance while improving rigidity.

[0117] In summary, this invention, by employing specific potassium titanate whiskers and compatibilizers and rationally controlling the addition amounts of each component, achieves synergistic effects among the components in both POM and UHMWPE base materials, resulting in a composite material with a lower coefficient of friction, higher surface hardness, and superior wear resistance. Furthermore, this material also possesses good mechanical properties and can be used in components such as automotive rearview mirror bearing cages and gears.

[0118] This invention illustrates the detailed process equipment and process flow through the above embodiments. However, this invention is not limited to the detailed process equipment and process flow described above, meaning that this invention does not necessarily depend on the detailed process equipment and process flow to be implemented. Those skilled in the art should understand that any improvements to this invention, equivalent substitutions of raw materials for the product of this invention, addition of auxiliary components, and selection of specific methods, all fall within the protection scope and disclosure scope of this invention.

Claims

1. A potassium titanate whisker-filled POM / UHMWPE composite material, characterized in that, The composite material comprises the following raw material components by weight: POM 60~80% UHMWPE 5~10% Potassium titanate whiskers: 10%~30% Lubricant 0.2%~0.5% Compound antioxidant 0.2%~0.5% The potassium titanate whiskers are modified potassium titanate whiskers obtained by sequentially treating with a pretreatment agent and a coupling agent; the pretreatment agent is (3-isocyanopropyl)triethoxysilane, and the coupling agent is methyloctadecyl(3-phenylpropyl)chlorosilane; the potassium titanate whiskers have a diameter of 0.2~0.6μm and a length of 10~20μm; the composite material also includes a compatibilizer, and the mass ratio of the compatibilizer to the potassium titanate whiskers is 1:(8~10); the compatibilizer is an ethylene terpolymer with a melt index of 20g / 10min at 190°C / 2.16 kg and a melting point of 80°C.

2. The potassium titanate whisker-filled POM / UHMWPE composite material according to claim 1, characterized in that, The POM has a melt flow index of 10-20 g / 10 min at 190°C / 2.16 kg.

3. The potassium titanate whisker-filled POM / UHMWPE composite material according to claim 1, characterized in that, The UHMWPE has a melt index of 3-7 g / 10 min at 190°C / 2.16 kg.

4. The potassium titanate whisker-filled POM / UHMWPE composite material according to claim 1, characterized in that, The modified potassium titanate whiskers are processed as follows: potassium titanate whiskers are reacted with a pretreatment agent to obtain intermediate potassium titanate whiskers, and intermediate potassium titanate whiskers are reacted with a coupling agent to obtain modified potassium titanate whiskers; the amount of the pretreatment agent added is 1.2~2.4% of the mass of the potassium titanate whiskers; the amount of the coupling agent added is 2~4% of the mass of the intermediate potassium titanate whiskers.

5. The potassium titanate whisker-filled POM / UHMWPE composite material according to claim 1, characterized in that, The lubricant is a mixture of copolymer and bead-like or flake-like wax.

6. The potassium titanate whisker-filled POM / UHMWPE composite material according to claim 1, characterized in that, The antioxidant is selected from one or more combinations of antioxidant 1076, antioxidant 1010, antioxidant CA, antioxidant 2246, antioxidant 168, antioxidant 1098, and antioxidant 626.

7. A method for preparing a potassium titanate whisker-filled POM / UHMWPE composite material as described in any one of claims 2-6, characterized in that, The preparation method includes: weighing the prescribed amounts of POM, UHMWPE, lubricant, compound antioxidant and compatibilizer and mixing them in a high-speed mixer to obtain a mixture; feeding the mixture from the main feed port of a twin-screw extruder; feeding potassium titanate whiskers from the side feed port; and extruding and granulating the mixture.

8. The preparation method according to claim 7, characterized in that, The twin-screw extruder has a processing temperature of 180~200 ℃, a screw speed of 240~360 r / min, a strip length through water of 1~2m, and a water temperature controlled at 20~40℃.

Citation Information

Patent Citations

  • Polyformaldehyde material for transmission and conduction parts and preparation method thereof

    CN102108182A

  • Crystal whisker reinforced poly(ether-ether-ketone) composite material and preparation method thereof

    CN105504763A

  • Polyurethane composite material as well as preparation method and application thereof

    CN121005857A